1993
DOI: 10.1002/pro.5560021219
|View full text |Cite
|
Sign up to set email alerts
|

P22 Arc repressor: Enhanced expression of unstable mutants by addition of polar C‐terminal sequences

Abstract: Many mutant variants of the P22 Arc repressor are subject to intracellular proteolysis in Escherichia coli, which precludes their expression at levels sufficient for purification and subsequent biochemical characterization. Here we examine the effects of several different C-terminal extension sequences on the expression and activity of a set of Arc mutants. We show that two tail sequences, KNQHE (st5) and H,KNQHE (st1 I), increase the expression levels of most mutants from 10-to 20-fold and, in some cases, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 26 publications
4
89
0
Order By: Relevance
“…63 The arc-st11 gene includes the coding sequence for the st11 C-terminal extension (H 6 KNQHE) to stabilize the proteins against degradation during expression and to allow for affinity purification. 64 Wild-type Arc and S-VLV proteins were overexpressed in Escherichia coli strain BL21(kDE3) cells transformed with the appropriate variant of pET800, and purified by Ni 2þ -NTA affinity chromatography under denaturing conditions by loading cleared cell lysates in 100 mM NaH 2 PO 4 (pH 8.0), 10 mM Tris, 6M guanidine hydrochloride, 10 mM imidazole onto 3 mL Ni 2þ -NTA resin per liter of culture, washing with 40, 40, and 20 mL fractions of the same lysis/loading buffer, and eluting with low pH using 6M guanidine hydrochloride containing 0.2M acetic acid. After elution, proteins were refolded by dialysis into SB250 buffer [50 mM Tris (pH 7.5), 250 mM KCl, 0.2 mM EDTA] for 48 h at 4 C, with one buffer change after 24 h.…”
Section: Mutagenesis Protein Expression and Affinity Purificationmentioning
confidence: 99%
“…63 The arc-st11 gene includes the coding sequence for the st11 C-terminal extension (H 6 KNQHE) to stabilize the proteins against degradation during expression and to allow for affinity purification. 64 Wild-type Arc and S-VLV proteins were overexpressed in Escherichia coli strain BL21(kDE3) cells transformed with the appropriate variant of pET800, and purified by Ni 2þ -NTA affinity chromatography under denaturing conditions by loading cleared cell lysates in 100 mM NaH 2 PO 4 (pH 8.0), 10 mM Tris, 6M guanidine hydrochloride, 10 mM imidazole onto 3 mL Ni 2þ -NTA resin per liter of culture, washing with 40, 40, and 20 mL fractions of the same lysis/loading buffer, and eluting with low pH using 6M guanidine hydrochloride containing 0.2M acetic acid. After elution, proteins were refolded by dialysis into SB250 buffer [50 mM Tris (pH 7.5), 250 mM KCl, 0.2 mM EDTA] for 48 h at 4 C, with one buffer change after 24 h.…”
Section: Mutagenesis Protein Expression and Affinity Purificationmentioning
confidence: 99%
“…It may be argued that the addition of the C-terminal (His)6 tag is responsible for the association behavior of the expressed [3etet peptides. However, C-terminally (His)6-tagged recombinant Arc repressor protein, which is of similar size (64 amino acids) and predicted secondary structure as the (His)6-tagged [3etc~ peptides, has virtually identical association properties and CD spectra as wild type Arc protein [25]. Thus, it is unlikely that the C-terminal (His)6 tag significantly affects the biochemical properties of the [3c~c~ peptides characterized in our study.…”
Section: Discussionmentioning
confidence: 73%
“…Previously, we had also shown that mutated protein Cop∆5, with a half-life of 31p6 min, is moderately less stable than wild-type CopR. Four of the C-terminal 7 aa and two of the C-terminal 5 aa are hydrophilic, which does support the role of hydrophilic amino acids in protecting more hydrophobic regions of the protein against proteolytic attack, as suggested by the publications of R. T. Sauer's group (Milla et al, 1993 ;Parsell & Sauer, 1989 ;Parsell et al, 1990). …”
Section: The C-terminal 7 Aa Contribute To Copr Stabilization By a Famentioning
confidence: 77%
“…Furthermore, residues closer to the C terminus appeared to play a greater role in determining the proteolytic susceptibility of the proteins than those farther away (Parsell et al, 1990). In all cases, however, the extensions were found to be unstructured and did not interact with the folded portions of the protein (Milla et al, 1993), and the stabilizing function was explained simply with the protection of hydrophobic parts of the proteins by these unstructured hydrophilic\ polar residues.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation